109:poster Were forcibly displaced people prioritized in the COVID-19 national response plans?. (28th April 2022) - Vélez, Claudia-Marcela; Kapiriri, Lydia; Danis, Marion; Goold, Susan; Nouvet, Elysee; Collaboration', GPSet
Abstract : Background: Forcibly displaced people represent a huge humanitarian problem globally. At the end of 2020, the total number was 82, 4 million; from those, 34, 4 million were refugees, asylum seekers, and Venezuelan displaced abroad. Forcibly displaced people were identified as priority populations during the pandemic due to their risk of being the last served populations with healthcare. This paper aimed to identify if this population was prioritized in the COVID-19 national response plans of a sample of 86 countries. Methods: This study is part of a document analysis of 86 COVID-19 national response plans, assessing the degree of comply to quality parameters of effective priority setting. One of the parameters included was the degree to which vulnerable populations such as forcibly displaced people were explicitly prioritized for receiving COVID-19 related interventions or for continuity of non-COVID healthcare services. The analysis involved assessing whether and how forcibly displaced people were prioritized in the COVID-19 national response plans. This was compared with the displaced populations identified in the host countries' UNHCR Forced Displacement 2020 report. Results: Only five countries among 86 analyzed prioritized forcibly displaced people in their COVID-19 national response plans. Among the top ten forcibly displaced people hosting countries, Uganda was the only one with an explicit prioritization of this vulnerable group. Although Turkey, Colombia, and Germany account for nearly one-fifth (6, 6 million) of refugees, asylum seekers and Venezuelans displaced abroad, none of the COVID-19 response plans of these countries prioritized these populations. Discussion: Few countries recognized forcibly displaced people as a vulnerable population in their COVID-19 response and preparedness plans. Governments may have incorporated actions and interventions for these vulnerable groups after publishing the COVID-19 response plans. It would be essential to evaluate the impact of this lack of prioritization on the health and wellbeing of these population groups.